Developing the moral competencies of accounting students: a case study of International Islamic University Malaysia (IIUM) - Umaru Zubairu (International Journal of Assessment Tools in Education)
Two decades of financial scandals have seriously damaged the credibility of accountants as guardians of financial information. To repair this credibility, the Malaysian government released a blueprint that mandated Malaysian educational institutions to produce morally competent professionals. This study sought to assist the accounting department at the International Islamic University Malaysia (IIUM) in achieving this mandate by evaluating the moral competencies of 2nd-year students enrolled in the department. The evaluation revealed that the students' had below par levels of moral competencies in dealing with ethical dilemmas in an accounting context. The implication of these results is that IIUM's accounting department has to critically assess the ethical content of its curriculum in order to ensure that it is capable of developing the moral competencies of these students to an excellent level. Additionally, there is a need for IIUM to institutionalize the measurement of students' moral competencies so that an objective determination can be made as to how effective the department is in developing the moral competencies of its students.